Dynamic modeling of idiosyncratic risk under economic sensitivity: A case of Pakistan - Hasan Hanif; Muhammad Naveed (Cogent Economics & Finance, 2020)
Financial institutions are an important source of providing impetus to investment by mobilizing savings and channelizing them to meet much needed capital requirements of other sectors. Similarly, the extant literature documents volatility of influential financial intuitions is not standalone but of contagious nature tending to spread through the financial system hence causes economic and financial shocks. This study brings new insights by investigating the dynamic aspect of idiosyncratic risk across different economic conditions in a developing economy like Pakistan. To analyze the impact of factors that influence idiosyncratic risk, one and two step system GMM is used. The findings of the study highlight that capital structure of the financial institutions needs proper monitoring of regulatory authorities as banks get a good amount of loans during good times but this can wreak havoc during the crisis as it happened in 2008-2009. In the like manner, the State Bank of Pakistan should also introduce higher liquidity requirements as results point out increased liquidity leads to lower level of idiosyncratic risk. In addition to that, Monetary policy and prudential regulation policy should also be aligned as contractionary monetary policy deters the munificence of the sector and leads to increase in external dynamism resulting in higher level of idiosyncratic volatility. The economic sensitivity analysis indicate that role of liquidity becomes more significant during crisis and postcrisis period. Finally, study also elucidates that sector level variables are also instrumental in modeling of idiosyncratic risk along with firm and country level variables.
Keywords: 330; dynamic model; economic sensitivity; Idiosyncratic risk; sector level variables